Latvian Women – Participants in the National Armed Resistance, 1940s–1950s - Dreimane, Inese (Genocidas ir rezistencija, 2024)
This article provides an insight into the participation of Latvian women in the armed national resistance movement after the Second World War. It is found that at least 414 Latvian women participated in the national partisan war of 1944–1956. Unlike men, they did not participate in military operations, but performed housekeeping work and medical duties.Women joined national partisan groups to avoid arrest because they had previously been partisan supporters. There were cases where women went to the forest because their family members were already there. In several cases, new families were also formed in the forest and children were born.
Keywords: Latvia; women; partisans; occupation; resistance